Dungeons & Dreamers - King, Brad; Borland, John (Play Story Press, 2026)
Before the multibillion computer game industry, there was Dungeons & Dragons, a tabletop game created by Gary Gygax and Dave Arneson in 1974. D&D captured the attention of a small but influential group of players, many of whom also gravitated to the computer networks that were then appearing on college campuses around the globe.With the subsequent emergence of the personal computer, a generation of geeky storytellers arose that translated communal D&D playing experiences into the virtual world of computer games. The result of that 40-year journey is today’s massive global community of players who, through games, have forged very real friendships and built thriving lives in virtual worlds. Dungeons & Dreamers follows the designers, developers, and players who built the virtual games and communities that define today’s digital entertainment landscape and explores the nature of what it means to live and thrive in virtual communities.